Alternative methods of obtaining silver from waste solutions using cementation. (1st September 2013) - Fabián, M.; Ficeriová, Jana; Briančin, J.; Harvanová, J.
Abstract : Thiosulphate leaching agent for silver is an alternative to cyanide leaching for certain types of refractory ores or secondary sources of the metal. Cementation of silver onto mechanically activated zinc powder after leaching is the most used method of the recovery of silver. The thiosulphate leaching of X-ray photos and cementation of silver by zinc from the solution are described in this paper. Application of cementation methods of processing silver from waste solutions represents economic as well as ecological importance for the whole society.